Effectiveness of government audit in ensuring accountability of clients in Zanzibar - Kassim, Rashid Mohamed (Mzumbe University, 2024)
A Dissertation submitted in partial fulfillments of the requirements for the award of Master of Science in Accounting and Finance of Mzumbe University